Mendorong Literasi Keuangan dan Inklusi Melalui Platform Digital: Pembelajaran bagi Guru Ekonomi - Uun Dwi Al Muddatstsir (Madaris: Jurnal Guru Inovatif, 2024)
In the current dynamic and complex era, understanding financial literacy and financial inclusion plays a pivotal role in shaping the well-being of individuals and society as a whole. This article discusses various aspects related to the understanding and implementation of these concepts in the context of economics education. Through in-depth analysis of literature, research, and related theories, this article delineates the role of economics teachers in promoting students' financial literacy and advocating for financial inclusion. The article highlights the challenges and issues faced by students regarding financial literacy and financial inclusion, as well as the impacts of insufficient understanding in the context of making prudent financial decisions. The article underscores the significance of collaboration among teachers, students, educational institutions, and the community to foster improved financial literacy and enhance financial inclusion. With a holistic approach, this article illustrates how effective and integrated economics education can mold a generation prepared to manage personal finances wisely, participate in an inclusive economy, and achieve sustainable prosperity.